The report of the commission on money and credit - BECKHART, B.H. (PSL Quarterly Review, 2014)
The Commission on Money and Credit was established in 1958 to study the financial and monetary structure of the United States for the purpose of determining whether it adequately serves its major economic objectives. In the course of its investigations, it examined the activities and policies of the Federal Reserve System, the fiscal and debt management policies of the Treasury, the work of private and federal credit institutions and the important problems involved in the coordination of monetary, credit and fiscal action. The present article provides an in-depth analysis of the report and its policy proposals. The author argues that the report suffers from a lack of a unifying theme with no specific task, and is generally superficial. Moreover, the Commission’s prescriptions would intensify cyclical swings instead of mitigating them and would destroy the Federal Reserve System as an effective instrument of monetary and credit policy. JEL: E40, E51, E52, E58